2016
DOI: 10.1016/j.appet.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Does milk matter: Is children’s intake affected by the type or amount of milk served at a meal?

Abstract: Increasing the energy density (ED) and portion size of foods promotes additional energy intake, but the effect of similar changes in milk is unknown. Using a crossover design, we tested the effect of varying the ED and portion size of milk served with lunch on preschool children's intake. Lunch was served in childcare classrooms on 4 days to 125 children aged 3-5 y (67 boys; 58 girls). Across the meals, milk was varied in ED (lower-ED [1% fat]; higher-ED [3.25% fat]) and portion size (100% [183 g]; 150% [275 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…Higher energy density will increase energy intake [ 4 ]. Children tend to reduce their volume intake when presented with higher energy density especially in boys [ 6 7 ]. Our study did show that energy intake was equal between groups regardless the energy density of ONS.…”
Section: Discussionmentioning
confidence: 99%
“…Higher energy density will increase energy intake [ 4 ]. Children tend to reduce their volume intake when presented with higher energy density especially in boys [ 6 7 ]. Our study did show that energy intake was equal between groups regardless the energy density of ONS.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which children differ in their susceptibility to overconsumption from large portions is also unclear. Shortterm studies of the portion size effect in children have found inconsistent effects for characteristics such as weight status (7,9,16,17), age (4,18), and eating behaviors (10,17,19,20). Thus, we investigated whether individual differences in these attributes affected the response to larger portions when intake was measured over a longer period of 5 d. Identifying characteristics that influence children's susceptibility to food properties such as portion size could assist in the development of targeted strategies for obesity prevention.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, no study has tried to compare the skim milk and whole milk in this regard. A recent study done by Kling et al [29] revealed that including full-fat milk in lunch decreases the amount of the lunch eaten by the children when compared with low-fat milk but the energy intake was not significantly different between the two beverages. In fact, they did not compare the effect of milk with different fat content on the satiety and energy intake in the subsequent meal.…”
Section: Discussionmentioning
confidence: 96%